2000
DOI: 10.1046/j.1365-2273.2000.00349.x
|View full text |Cite
|
Sign up to set email alerts
|

Sinus symptom scores: what is the range in healthy individuals?

Abstract: Patient symptom severity is an important outcome measure in the assessment and staging of chronic rhinosinusitis. Symptom scores based on a visual analogue scale (VAS) are being used increasingly for this purpose although little, if any, information is available on normal values for these scores. We assessed symptom score ratings using the ICSD symptom scores system (maximum score = 60), in a group of 100 healthy individuals who considered themselves free of nasal conditions. Scores from this healthy sample we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 12 publications
0
23
0
1
Order By: Relevance
“…The potential power of this approach is manifested by full discriminative ability of the genomic signature as early as 53 hours post-viral exposure, at a time when the average clinical score of symptomatic individuals is only 2.4. Symptoms of this nature and severity are clinically vague and would be typical of very mild allergies [22] or even symptoms due to sequelae of chronic smoking [23]. Therefore, genomic analyses demonstrate the potential to identify viral infection either before symptoms emerge or among what otherwise are common, nonspecific upper respiratory symptoms, when early intervention with antiviral medications could have profound impact on both individual symptoms and disease transmission [24], [25], [26].…”
Section: Discussionmentioning
confidence: 99%
“…The potential power of this approach is manifested by full discriminative ability of the genomic signature as early as 53 hours post-viral exposure, at a time when the average clinical score of symptomatic individuals is only 2.4. Symptoms of this nature and severity are clinically vague and would be typical of very mild allergies [22] or even symptoms due to sequelae of chronic smoking [23]. Therefore, genomic analyses demonstrate the potential to identify viral infection either before symptoms emerge or among what otherwise are common, nonspecific upper respiratory symptoms, when early intervention with antiviral medications could have profound impact on both individual symptoms and disease transmission [24], [25], [26].…”
Section: Discussionmentioning
confidence: 99%
“…Secondary outcomes included changes in methacholine reactivity, asthma symptoms (Asthma Symptom Utility Index [ASUI]), 25 asthma-related quality of life questionnaires (Childhood Health Survey for Asthma [CHSA] 26 or Marks Asthma Quality of Life Questionnaire [Marks AQLQ] 27 ), sinusitis and rhinitis symptoms including a sinus symptom questionnaire 28 and sinusitis related quality of life questionnaires ( SinoNasal survey-5 [SN5] 29 for 6-17 years, and SinoNasal Outcome Test 22 [SNOT22] 30 for 18 years and older), spirometry and exhaled nitric oxide. Secondary outcomes also included the rate of acute episodes of poor asthma control defined as a decrease of greater than 30% in morning peak flow rate from personal best (assessed during run-in) for 2 consecutive days, addition of an oral corticosteroid to treat asthma symptoms, unscheduled contact with a health care provider for asthma symptoms or increased use of short acting β-agonists (≥ 4 additional puffs of rescue medication or ≥2 additional nebulizer treatments in 1 day).…”
Section: Methodsmentioning
confidence: 99%
“…However, work on scoring systems in otolaryngology and indeed the research we have carried out has clearly demonstrated that this is not the case. 9 The work done by Walker and White using the International Conference on Sinus Disease scoring system for rhinosinusitis showed that the average score in asymptomatic adults was greater than the minimum score and that there was substantial overlap between the scores of symptomatic and asymptomatic individuals. 9 We can only speculate about the reasons for our findings.…”
Section: Discussionmentioning
confidence: 99%
“…9 The work done by Walker and White using the International Conference on Sinus Disease scoring system for rhinosinusitis showed that the average score in asymptomatic adults was greater than the minimum score and that there was substantial overlap between the scores of symptomatic and asymptomatic individuals. 9 We can only speculate about the reasons for our findings. It is possible that there is a background incidence of shoulder pathology in the general population that never requires medical intervention.…”
Section: Discussionmentioning
confidence: 99%